Traditional Kucing-Kucingan Game, in Improving Ground Motor Skills to Blind Children in SLB Negeri A Citeureup Cimahi - Nikmal Maula; Zulkifli Sidiq (INCLUSIVE EDUCATION, 2022)
Untrained gross motor skills in children with visual impairment, especially on the walking and balance motion will hinder the mobility process in children, thus forming walking motion and posture that is not good for the children. This circumstance certainly cannot be tolerated because it can interfere the children's motor development. Therefore, it is necessary to get proper and professional management to be able to overcome these problems so that children with visual impairment can have good mobility. This difficulty was experienced by subject with the initials I grade 1 at SDLBN A Citeureup, Cimahi. One of the efforts that can be done to intervene this case is by applying the traditional Kucing-kucingan game. This research aims to determine how much improvement is given by the traditional Kucing-kucingan toward gross motor skills in children with visual impairment, especially in aspects of walking and balance motion, This research uses experimental method with Single Subject Research Design A-B-A. The data obtained starting from baseline-1 (A-1), intervention (B), and baseline-2 (A-2) conditions. The presentation of data is processed and analyzed using descriptive statistics. The results showed that the ability of student (I) in doing the walking and balance motion was increased after the given intervention using traditional Kucing-kucingan game. Therefore, the researcher recommends this traditional Kucing-kucingan game to educators so they can consider the traditional Kucing-kucingan game as an alternative in conducting activities during free hours in order to improve gross motor skills in children with visual impairment, due to interesting games for children will greatly assist the continuity of activities process. Traditional game, especially kucing-kucingan, is considered effective when it is used properly to increase the children's interest in moving freely.